Carolus Linnaeus and the Edible Dormouse - Carlo Violani (Hystrix, the Italian Journal of Mammalogy, 1995)
Abstract Carolus Linnaeus was totally unacquainted with the Edible Dormouse Myoxus glis (L.), a species not found in Sweden: while describing Mus Rattus in the 10th Edition of the "Systema Naturae" (1758), the Swedish naturalist confessed his ignorance concerning the "Glis" of the ancients and suggested that it might have been the marmot or the hamster. Thanks to written information received from his correspondent in Slovenia, Giovanni Antonio Scopoli, Linnaeus was able to include the new species Sciurus Glis in his 12th Edition of the "Systema Naturae" (1766), reporting almost verbatim a summary of Scopoli's description of the rodent. Scopoli's letter is still preserved in the Library of the Linnean Society of London. The Linnean type locality "Habitat in Europa australi" for the Edible Dormouse Myoxus glis glis must therefore be restricted to "Southern Carniola, Slovenia", contra "Germany" as stated, for instance, by Miller (1912), Toschi (1965), Corbet (1978) and Storch (1978). A new name is required for the continental European form, for which M. glis germanicus ssp. nov. is here proposed. Some information on the appreciation of Myoxus glis as a delicacy ("carnes avide eduntur" in Linnaeus' words) conclude the paper. Riassunto Carlo Linneo ed il Ghiro - Dopo aver descritto Mus Rattus nella decima edizione del "Systema Naturae" (1758) il naturalista svedese Carlo Linneo confessava di non essere a conoscenza del "Glis" degli antichi autori e ne suggeriva l'identificazione con la Marmotta o con il Criceto comune; è infatti noto che Myoxus glis non è diffuso in Svezia. In base ad una lettera ricevuta dal suo corrispondente in Slovenia, Giovanni Antonio Scopoli, Linneo fu in grado di descrivere questa nuova specie come Sciurus Glis nella dodicesima edizione del "Systema Naturae" (1766), riportando quasi parola per parola un sunto della descrizione latina del Ghiro comunicatagli da Scopoli. La lettera di Scopoli si trova ancora oggi nella biblioteca della Linnean Society di Londra. La località tipica per il Ghiro Myoxus glis glis "Habitat in Europa australi" di Linneo deve essere quindi ristretta alla Carniola meridionale, Slovenia; "Germania" indicata da numerosi autori (cfr. Miller, 1912; Toschi, 1965; Corbet, 1978; Storch, 1978) è dunque errata. Per la forma dell'Europa continentale il nome di Myoxus glis germanicus ssp. nov. viene proposto in questa sede. Alcune notizie sulla commestibilità delle carni del Ghiro ("carnes avide eduntur" secondo le parole stesse di Linneo) concludono il lavoro.